Penerapan Media Pembelajaran Konkret Diorama Rantai Makanan untuk Meningkatkan Hasil Belajar IPAS Materi Rantai Makanan pada Peserta Didik Kelas 5 SD Negeri Tunggulsari 2 Surakarta - Setiasih, Clara Hernika; Pratiwiningrum, Yunita; Riyadi, Riyadi (Universitas Sebelas Maret, 2024)
The purpose of this study is to investigate how food chain diorama media might enhance the science learning outcomes of fifth-grade students at SDN Tunggulsari 2 Surakarta. Dioramas are three-dimensional representations of scenes that pique students' curiosity and arouse their emotions. Tests, observations, and documentation were some of the qualitative and quantitative data-gathering techniques used in this classroom action research (CAR). The Milles and Hubberman interactive model was used for data analysis, and method triangulation was used to guarantee data quality. Findings indicated that learning outcomes for students had significantly improved; completion rates had gone from 22.2% in the pre-cycle to 61.1% in cycle 1 and 88.9% in cycle 2.